2018
DOI: 10.3389/fpsyg.2018.01952
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Personality and Child Temperamental Reactivity: Differential Susceptibility for Child Externalizing Behavioral Problems in China

Abstract: It is important to identify the developmental antecedents of externalizing behavioral problems in early childhood. The current study examined the main effects of maternal personality and its interactive effects with child temperamental reactivity in predicting child externalizing behavioral problems, indicated by impulsivity and aggression. This study was composed of 70 children (Mage = 17.6 months, SD = 3.73) and their mothers. The results showed that maternal agreeableness was negatively associated with chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Although, as noted, most of these studies focused on a negative-neutral range of the environmental aspect and did not include aspects of positive parenting or home environment. Other studies found evidence of differential susceptibility in predicting ADHD symptomatology, meaning that susceptible individuals were more sensitive to both negative and positive aspects of the environment (12, 13); such a pattern was also found in a study that examined impulsivity behaviors, which are considered a main symptom domain of ADHD, but ADHD symptoms were not fully assessed (22). Other studies found evidence of a vantage sensitivity pattern (15,101), meaning that some individuals were sensitive only to positive, or less negative, aspects of the environment.…”
Section: Interim Summarymentioning
confidence: 71%
See 4 more Smart Citations
“…Although, as noted, most of these studies focused on a negative-neutral range of the environmental aspect and did not include aspects of positive parenting or home environment. Other studies found evidence of differential susceptibility in predicting ADHD symptomatology, meaning that susceptible individuals were more sensitive to both negative and positive aspects of the environment (12, 13); such a pattern was also found in a study that examined impulsivity behaviors, which are considered a main symptom domain of ADHD, but ADHD symptoms were not fully assessed (22). Other studies found evidence of a vantage sensitivity pattern (15,101), meaning that some individuals were sensitive only to positive, or less negative, aspects of the environment.…”
Section: Interim Summarymentioning
confidence: 71%
“…2 Specifically, high reactive children whose mothers had high levels of conscientiousness showed the lowest levels of impulsivity, even compared to low reactive children. However, high reactive children whose mothers had lower conscientiousness showed the highest levels of impulsivity, suggesting a pattern of differential susceptibility (22).…”
Section: Sensitivity To Positive Aspects Of the Home Environmentmentioning
confidence: 94%
See 3 more Smart Citations